Non-Occlusive Mesenteric Ischemia in Cardiac Arrest Patients - Smalcova, Jana; Belohlavek, Jan (Reviews in cardiovascular medicine, 2023)
Non-occlusive mesenteric ischemia (NOMI) is a severe complication in patients after cardiac arrest (CA). The diagnosis is complicated, the treatment options are limited. Given the susceptibility of enterocytes to ischemia, the incidence and severity of NOMI in the post-resuscitation period may reflect the intensity and duration of both ischemia and subsequent reperfusion injury. NOMI is considered to be associated with adverse neurological outcomes in CA patients. Therefore, NOMI should not only be regarded as a post-resuscitation complication but also as one of the prognostic markers in CA patients.This paper summarizes current knowledge on NOMI's pathophysiology, diagnosis, treatment, and prognostic significance in CA patients.
Keywords: non-occlusive mesenteric ischemia; cardiac arrest; ischemia-reperfusion injury